Potentials of load-shifting with renewable energy storage: An environmental and economic assessment for the UK - Chowdhury, Jahedul Islam; Balta-Ozkan, Nazmiye; Goglio, Pietro; Hu, Yukun; Varga, Liz; McCabe, Leah (US Association for Energy Econimics, 2018)
The Paris Agreement set targets to limit global warming to less than 2°C above the pre-industrial level to significantly reduce the risks and impacts associated with climate change [1]. Globally, the energy supply sector is responsible for 25% of greenhouse gas (GHG) emissions [2]. In addition to ratifying Paris Agreement, the UK government has adopted legally binding 80% emissions reduction target from 1990 levels by 2050 as outlined in Climate Change Act. The decarbonisation of power supply, along with electrification of heat and transport, are highlighted as key elements of this transition by both policy and academic research [3]–[5]. Storage systems, via the multiple services they offer across the electricity supply chain [6] at different operational scales stand to create system-wide benefits, enhanced flexibility and reliability for effective management of the grid [7]. The potential contributions storage systems can make towards minimizing the carbon intensity of UK grid with high levels of renewables is recognised by the government as well [8]. This study aims i) to determine the amount of load shifting that can be achieved by the combination of current renewable energy mainly wind and solar and UK grid level storage, ii) analyse the amount of renewable energy generation and storage (RES) needed to phase out programmable gas power generation during the periods of peak demand and iii) assess their economic and environmental implications. The environmental impacts considered are the life cycle emissions associated with electricity generation from the UK mix and the production, installation and use of batteries. The analysis will be extended to cover the future energy scenarios.